Correlation between formative assessments and final examination performance in a statistics course / Siti Balqis Mahlan ... [et al.] - Mahlan, Siti Balqis; Hamat, Muniroh; Shamsuddin, Maisurah; Umar, Norazah (Unit Penerbitan JSKM, 2025)
This study investigates the correlation between formative assessments and final examination performance in a statistics course. The assessments include quizzes, tests, and group assignments, with the final exam serving as the dependent variable. A Pearson correlation analysis was conducted on a sample of 26 students. The findings reveal that Group Assignment has the highest correlation with the Final Exam (r = 0.597, p < 0.05), followed by Test (r = 0.554, p < 0.05), while Quiz shows no significant correlation (r = 0.345, p = 0.085 (p > 0.05)). Although Group Assignment exhibits the strongest correlation, its group-based nature may not accurately reflect individual student performance. In contrast, Test, conducted individually, emerges as a more reliable predictor of final exam outcomes despite its slightly lower correlation. Descriptive statistics indicate that Group Assignment has the highest mean score (84.885) while Quiz has the highest variability (SD = 17.6947). These results highlight the importance of considering assessment structure when evaluating student performance. The study provides insights for educators on optimizing formative assessments to enhance students’ preparedness for summative evaluations